2014
DOI: 10.1001/jama.2014.11026
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine for Prevention of Postpericardiotomy Syndrome and Postoperative Atrial Fibrillation

Abstract: MD; for the COPPS-2 Investigators IMPORTANCE Postpericardiotomy syndrome, postoperative atrial fibrillation (AF), and postop-erative effusions may be responsible for increased morbidity and health care costs after cardiac surgery. Postoperative use of colchicine prevented these complications in a single trial. OBJECTIVE To determine the efficacy and safety of perioperative use of oral colchicine in reducing postpericardiotomy syndrome, postoperative AF, and postoperative pericardial or pleural effusions. DESIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
226
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 298 publications
(244 citation statements)
references
References 23 publications
6
226
0
12
Order By: Relevance
“…Inne metody leczenia również oceniano w małych próbach klinicznych generujących nowe hipotezy badawcze, ale nie wykazano jednoznacznie ich korzystnych efektów. Do ocenianych metod należało stosowanie magnezu [925,935,936], wielonienasyconych kwasów tłuszczowych z grupy omega-3 [937][938][939][940][941][942][943][944][945], kolchicyny [946] i glikokortykosteroidów [947,948], a także wycięcie tylnej części osierdzia [949]. Pooperacyjna stymulacja dwuprzedsionkowa narzuconym szybkim rytmem (overdrive) nie znalazła powszechnego zastosowania mimo pewnych danych wskazujących na jej profilaktyczny efekt [925,950].…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified
“…Inne metody leczenia również oceniano w małych próbach klinicznych generujących nowe hipotezy badawcze, ale nie wykazano jednoznacznie ich korzystnych efektów. Do ocenianych metod należało stosowanie magnezu [925,935,936], wielonienasyconych kwasów tłuszczowych z grupy omega-3 [937][938][939][940][941][942][943][944][945], kolchicyny [946] i glikokortykosteroidów [947,948], a także wycięcie tylnej części osierdzia [949]. Pooperacyjna stymulacja dwuprzedsionkowa narzuconym szybkim rytmem (overdrive) nie znalazła powszechnego zastosowania mimo pewnych danych wskazujących na jej profilaktyczny efekt [925,950].…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified
“…934 Other therapies have also been studied in small, hypothesis-generating trials, but have not demonstrated clear beneficial effects. These include magnesium, 925,935,936 n-3 polyunsaturated fatty acids, 937 -945 colchicine, 946 corticosteroids, 947,948 and posterior pericardectomy. 949 Post-operative overdrive biatrial pacing has not gained widespread use despite some suggestion of prophylactic effects.…”
Section: Prevention Of Post-operative Atrial Fibrillationmentioning
confidence: 99%
“…Experimental and observational clinical data supported reninangiotensin-aldosterone blockers in AF prevention schemes 28,29 , but subsequent large randomized trials did not demonstrate a clinical benefit in patients without an established indication for these substances 30,31 . Drugs with anti-inflammatory and antioxidative properties that were tested for the prevention of AF in several settings showed mixed outcomes 23,[32][33][34][35] . Finding markers for the major disease mechanisms -or 'health modifiers' -causing AF in a given patient would enable some of these treatment modalities to be used successfully.…”
mentioning
confidence: 99%